Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Akhlakul Karimah Siswa Kelas VIII SMP Bhina Sosial Jati Agung Lampung Selatan Tahun Pelajaran 2025/ 2026 : Penelitian - Ahsena Lutfi Afifah; Fahri Aryanto; Eha Julaeha; Ria Asnani; Rina Setyaningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the strategies used by Islamic Religious Education (IRE) teachers in improving the noble character (akhlakul karimah) of eighth-grade students at SMP Bhina Sosial Jati Agung, South Lampung, in the 2025/2026 academic year. The background of this research is the crucial role of IRE teachers in shaping students’ character and morals amid the challenges of modern times. This research employed a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that IRE teachers apply several strategies, including setting good examples in attitudes and behavior, habituating religious activities at school, providing advice and motivation, and implementing contextual learning methods based on the values of akhlakul karimah. These strategies proved effective in fostering students’ discipline, responsibility, politeness, and social awareness. The study concludes that the success of improving akhlakul karimah is strongly influenced by the consistency of IRE teachers in implementing sustainable strategies, supported by the school environment and family.